Optimizing treatment selection and sequencing decisions for first-line maintenance therapy of newly diagnosed advanced ovarian cancer - International considerations amongst upper middle- and high-income countries (UMIC and HIC) - Jeffrey C.H. Goh; Charlie Gourley; David S P Tan; Angélica Nogueira-Rodrigues; Hesham Elghazaly; Marc Edy Pierre; Gonzalo Giornelli; Byoung-Gie Kim; Flavia Morales-Vasquez; Alexandra Tyulyandina (Elsevier, 2022)
The incidence and mortality rates of ovarian cancer are increasing globally. Ovarian cancer is diagnosed at an advanced stage in 80% of women. After standard, platinum-based, front-line chemotherapy, poly (ADP-ribose) polymerase (PARP) inhibitors and antiangiogenic agents are successfully employed as maintenance strategies for newly diagnosed, advanced ovarian cancer patients. Landmark clinical studies, including SOLO-1, PAOLA-1, PRIMA, and VELIA, have provided crucial insights on optimizing first-line maintenance treatment using PARP inhibitors. A group of ovarian cancer experts, (primarily from upper middle & high income countries outside US, China, Japan & Europe) met in September 2019 to discuss new developments for the first-line treatment of ovarian cancer and its implications.Key implications of the evolving clinical data included: (1) olaparib or niraparib maintenance therapy appears to be the preferred choice for patients with BRCA1/2 mutations; hence, BRCA testing is beneficial in identifying these patients; (2) niraparib monotherapy and olaparib in combination with bevacizumab have demonstrated significant benefit in progression-free survival (PFS) in homologous recombination deficiency (HRD)-positive patients; (3) bevacizumab, niraparib alone, or observation can be an alternative for HRD-negative patients; (4) further data is warranted to explore the role of PARP inhibitors in treating HRD-negative, ovarian cancer patients to confirm findings of the exploratory analysis of PRIMA; (5) PARP inhibitors may be beneficial for stage IV ovarian cancer patients with inoperable disease and patients with prior neoadjuvant chemotherapy; and (6) there is an urgent need to increase awareness in both clinicians and patients on BRCA and HRD testing for optimizing treatment decision-making and improving clinical outcomes in newly diagnosed, advanced ovarian cancer patients. In clinical medicine, the limited availability of family history (FH) information and the complexity of FH criteria has hampered the implementation of BRCA testing. Moreover, many cancer patients with BRCA mutations are not tested because they do not meet the criteria for FH. Consequently, BRCA testing in many high income countries, including the US and Australia, is underused and used inappropriately, which has resulted in the loss of valuable opportunities for better cancer management and cancer prevention.